Management of Peritonsillar Abscesses in Adults: Survey of Otolaryngologists in Canada and the United States. Issue 3 (September 2021) - Forner, David; Noel, Christopher W.; Grant, Amy; Hong, Paul; Corsten, Martin; Wu, Vincent; Taylor, S. Mark; Trites, Jonathan R. B.; Rigby, Matthew H.
Objective: The management of peritonsillar abscess (PTA) has evolved over time. We sought to define contemporary practice patterns for the diagnosis and treatment of PTA. Study Design: Cross-sectional survey. Setting: The 15-question survey was distributed to members of the Canadian Society of Otolaryngology–Head and Neck Surgery (CSO) and the American Academy of Otolaryngology–Head and Neck Surgery (AAO-HNS). Methods: An iterative, consensus-based process was used for survey development. Primary outcomes were to determine methods of diagnosis and first-line treatments for PTA. Exploratory, secondary outcomes were analyzed using multivariable logistic regression models. Results: The survey response rate was 12.6% (n = 1176). Most participants were attending staff (86%) in a community hospital setting (60%) and had been in practice for more than 20 years (38%). Most respondents (78%) indicated that at least half of the time, cross-sectional imaging had already been performed before they were consulted. Half of respondents (49%) indicated that they perform incision and drainage of the abscess as first-line treatment, while few (16%) provide medical management alone. In exploratory analysis, participants from the AAO-HNS had higher odds of imaging already being performed before consultation (odds ratio [OR], 11.7; 95% CI, 4.6-29.4) and increased odds of using medical management alone as a first-line treatment (OR, 2.4; 95% CI, 1.3-4.2) compared to respondents from the CSO. Conclusion: There is wide practice variation in the diagnosis and management of acute, uncomplicated PTA among otolaryngologists in Canada and the United States. The use of cross-sectional imaging and medical management alone may differ between countries of practice.